Growth arrest is a DNA damage protection strategy in Arabidopsis - Antonio Serrano-Mislata; Jorge Hernández-García; Carlos de Ollas; Noel Blanco-Touriñán; Silvia Jurado-García; Cristina Úrbez; Aurelio Gómez-Cadenas; Robert Sablowski; David Alabadí; Miguel A. Blázquez (Nature Communications)
Abstract When exposed to stress, plants reduce growth while activating defense mechanisms—a behaviour proposed to help reallocate resources and meet the energy demands required for survival. Here, we have challenged this view by mutating the cyclin-dependent kinase inhibitor SMR1 to reverse the growth arrest imposed by high DELLA levels. These plants continue growing under limited water availability but maintain the same oxidative stress tolerance and survival rates as the parental line that halted growth. However, shoot and root meristematic cells that keep dividing under drought or genotoxic stress accumulate DNA damage, frequently leading to cell death. Since the DNA lesions are observed in the apical stem cells that give rise to all plant organs, including flowers, we propose that systemic growth arrest acts as a defense strategy that plants employ not only to maximize individual fitness, but also to ensure the accurate transmission of genetic information to their progeny.